Sanitary Landfill Siting Using GIS and AHP: A Case Study in Johor Bahru, Malaysia - Mohammed, H. I.; Majid, Z.; Yamusa, Y. B.; Mohd Ariff, M. F.; Idris, K. M.; Darwin, N. (Engineering, Technology & Applied Science Research, 2019)
One of the major problems affecting municipalities is solid waste management. There is a difficulty in selecting suitable sites for waste disposal as it involves different factors to be considered before site selection. Currently, waste generation in Johor Bahru has steadily increased over the last few years and the only existing sanitary landfill is reaching its capacity limits, which means that a new sanitary landfill site needs to be constructed. In this study, geographic information system (GIS) and analytical hierarchy process (AHP) methods were utilized with the integration of dynamic data such as future population and projection of waste production in order to provide suitable sites for the construction of a sanitary landfill in the study area. Thirteen criteria were considered for this study, namely water bodies, soil, geology, slope, elevation, residential areas, archeological sites, airports, population, road, railway, infrastructure, and land use. AHP was used to determine the weights for each criterion from the pairwise comparison matrix. Consistency index and consistency ratio were checked and confirmed to be suitable. The results obtained from AHP were assigned to each criterion in GIS environment using weighted overlay analysis tool. The final potential site map was produced, and the three most suitable potential landfill sites were identified.